A Spherical Harmonic Model of Earth's Lithospheric Magnetic Field up to Degree 1050. Issue 21 (5th November 2021) - Thébault, E.; Hulot, G.; Langlais, B.; Vigneron, P.
Abstract: Detailed mapping of the Earth's magnetic field brings key constraints on the composition, dynamics, and history of the crust. Satellite and near‐surface measurements detect different length scales and are complementary. Here, we build a model, selecting and processing magnetic field measurements from the German CHAMP and ESA Swarm satellites, which we merge with near‐surface scalar anomaly data. We follow a regional approach for modeling the magnetic field measurements and next transform the series of regional models into a unique set of spherical harmonic (SH) Gauss coefficients. This produces the first global model to SH degree 1050 derived by inversion of all available measurements. The new model agrees with previous satellite‐based models at large wavelengths and fits the CHAMP and Swarm satellite data down to expected noise levels. Further assessment in the geographical and spectral domains shows the model to be stable when downward continued to the Earth's surface. Plain Language Summary: The magnetic field of the Earth's results from the superposition of various internal and external fields. The field produced by magnetized rocks in the Earth's lithosphere brings essential constraints on the crust composition, dynamics, and history. Its description requires magnetic measurements in all regions of the world at different altitudes. Satellite measurements detect well the large Earth's magnetic field structures but are too far to detect the smaller ones that are weak at high altitudes. Historical marine and airplane data can be used to complement the satellite observations. Considering all these data makes it possible to build a global model that represents the magnetic field generated within the Earth's crust with a global 40 km horizontal spatial resolution. Key Points: Model based on a joint inversion of Swarm and CHAMP satellites magnetic field measurements and near‐surface scalar anomaly gridded data First global lithospheric vector magnetic field model at the Earth's mean radius to about 40 km resolution